2008
DOI: 10.1093/jhered/esm120
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Origin of Leatherback Turtles (Dermochelys coriacea) from the Brazilian Coast

Abstract: The leatherback sea turtle (Dermochelys coriacea) population that nests in Brazil is restricted to a few individuals, but high densities of pelagic individuals are observed along the southern and southeastern Brazilian coast. We investigated the diversity of the mitochondrial DNA (mtDNA) control region in order to understand the relationship between nesting and pelagic leatherbacks from Brazil and elsewhere. High-quality 711-bp sequences were generated, analyzed, and compared with published data from worldwide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 23 publications
6
41
3
1
Order By: Relevance
“…Analysis of the control region, a more variable gene, revealed the signature of some structure between French Guiana and French West Indies, which contrasts with the previous study showing the presence of only one 496 bp haplotype in the Guianas and three haplotypes in the West Indies [36]. These differences could be explained by the longer sequences used in this study, hence improving the resolution of mtDNA for comprehensive phylogeographic studies [32].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Analysis of the control region, a more variable gene, revealed the signature of some structure between French Guiana and French West Indies, which contrasts with the previous study showing the presence of only one 496 bp haplotype in the Guianas and three haplotypes in the West Indies [36]. These differences could be explained by the longer sequences used in this study, hence improving the resolution of mtDNA for comprehensive phylogeographic studies [32].…”
Section: Discussioncontrasting
confidence: 97%
“…The leatherback turtle's life cycle involves pluriannual migrations after the nesting periods [23], [24] and female natal homing behavior [25], [26], and this complexity makes the issues of population dynamics and status difficult to address. Nevertheless, our understanding of phylogeographic patterns, population dynamics and behavior in sea turtles has been greatly improved thanks to molecular markers [26][32]. Autosomal microsatellite variability has been shown to provide relevant estimates of both the timescale and strength of past demographic events [33], [34] thus allowing the assessment of recent changes in population size and potential recovery [17], [35].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to haplotype diversity, which increased due to the fact that more polymorphic sites were found, nucleotide diversity using the longer fragment did not increase likely because almost twice the number of nucleotides was screened. Similar results were obtained in hawksbill (Eretmochelys imbricata) and leatherback (Dermochelys coriacea) studies, where additional variable sites and the splitting of common previously lumped haplotypes were revealed using the longer segments (Abreu- Grobois et al 2006;Velez-Zuazo et al 2008;Vargas et al 2008). …”
Section: Demographic History Of Loggerheads Nesting In Cape Verdesupporting
confidence: 77%
“…Genetic and tag recovery data have shown that leatherbacks and loggerheads incidentally captured in fisheries or stranded on adjacent south-west Atlantic beaches are of mixed stocks, with individuals from nesting populations from Brazil, east Atlantic-Africa, Indian Ocean, Australia, North Atlantic and unknown origins (Billes et al, 2006;Sales et al, 2008;Vargas et al, 2008), making sea turtle conservation in south-west Atlantic waters of global importance.…”
Section: Implications For Fishery Management and Conservationmentioning
confidence: 99%